Analisis Penerapan Etika Bisnis Dalam Perusahaan: Studi Literatur Faktor Pendukung Dan Tantangan - Nayli Amirah Firdaus; Ilham Takbir Al Azhiim; Veda Ardellia (Lembaga Pengembangan Kinerja Dosen, 2023)
This journal conducts an analysis of the implementation of business ethics in companies, focusing on supporting factors and challenges faced. In an era of rapid industrial growth, companies are confronted with intense competition, shifting customer preferences, environmental sustainability, and a shortage of quality human resources. The application of business ethics becomes crucial in adhering to established rules and norms, building corporate reputation, and achieving long-term success. Additionally, it is important to consider the impact of the company's information systems on society and to apply ethical principles in the use of algorithms and artificial intelligence. Through literature analysis, this journal provides recommendations and guidelines for business practitioners currently operating their businesses.